Redescription of the type species of Strandesia Stuhlmann, 1888 and Cypricercus Sars, 1895 (Crustacea, Ostracoda, Cypricercinae), with a description of a new species of Cypricercus from South Africa - Savatenalinton, Sukonthip; Martens, Koen (Zootaxa, 2009)
We redescribe Cypricercus cuneatus Sars, 1895 and Strandesia mercatorum (Vavra, 1895), type species of their genera, in order to reassess the taxonomic position of species in Cypricercus s.l. and Strandesia s.l., as well as to clarify the distinction between Cypricercus s.s. and Strandesia s.s. The morphology, taxonomy and zoogeography of these two genera are discussed. Strandesia amati (Martens, 1984) is synonymised with Strandesia lineata Victor & Fernando, 1981. Strandesia trispinosa galantis Broodbakker, 1983 becomes a synonym of the nominotypical form. Cypricercus inermis (Brady, 1904) is herewith redescribed and reinstated as a valid species, not synonymous to the type species of the genus as was previously thought. One Cypricercus (C. salinus De Deckker, 1981) and eleven Strandesia (S. crassa Klie, 1939, S. dani George & Martens, 1993, S. decorata (Sars, 1903), S. lineata Victor & Fernando, 1981, S. parva Hartmann, 1964, S. tolimensis Roessler, 1990, S. trichurensis Victor et al., 1980, S. trispinosa (Pinto & Purper, 1965), S. tuberculata Hartmann, 1964, S. umbonata Victor & Fernando, 1981, S. weberi (Moniez, 1892)) are allocated to Bradleystrandesia. Cypricercus mongolicus Daday, 1909 is transferred to Eucypris. Cypricercus xhosa sp. nov. is here described from South Africa. We also propose a conservative list of species belonging to Cypricercus s.s. and Strandesia s.s.